Standardization of planting date for potato (Solanum tuberosum) breeder seed production in Gwalior region of north central india under prevailing climatic situations - SADAWARTI, MURLIDHAR J; PANDEY, K K; SAMADHIYA, R K; SINGH, S P; ROY, S (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted at the Central Potato Research Station, Gwalior, Madhya Pradesh during 2012-13, 2013-14 and 2014-15 for standardization of planting date for Potato (Solanum tuberosum L.) breeder seed production with five planting dates, viz. 10 October, 17 October, 24 October, 31 October and 7 November with three popular varieties namely Kufri Chandramukhi (early medium), Kufri Sindhuri (late) and Kufri Chipsona-1(medium). The experiment was planted in three replication in split plot design. Seed production was done as per standard seed plot technique. Days to emergence were significantly delayed in 2012-13 and in 10 October (10.4 days) planting. Final emergence was significantly higher in 2014-15 (93.27%) and in 7 November (91.93%) and in Kufri Sindhuri (91.19%). 2014-15 planting and Kufri Sindhuri and Kufri Chipsona 1 recorded significantly higher growth attributing parameters, viz. stem number, compound leaves and plant height. Significantly higher stem number were recorded in 24 October (4.2) and onward planting. All the other four date of planting recorded significantly higher compound leaves/plant over 31 October planting (38). Decreasing trend in case of plant height was recorded with delay in planting.Significantly higher total tuber number and yield/ha was recorded in planting year 2013-14 and from 24 October, 31 October and 7 November planting over other two earlier planting date and highest was in 7 November planting date (634 thousand/ha and 25.39 tonnes/ha). Significantly higher tuber number and weight was recorded in Kufri Sindhuri (669 thousand/ha and 23.87 tonnes/ha) and Kufri Chipsona 1 (551 thousand/ha and 23.87 tonnes/ha) over Kufri Chandramukhi. Severe mosaic, mild mosaic and off type in each date of planting and varieties were far below maximum permissible limit under Indian minimum seed certification standards. Aphid population (weekly) were below critical limit in all the planting years, date of planting and varieties and lowest was found in year 2014-15, 31 October and 7 November planting and in Kufri Chandramukhi, respectively. Breeder seed production under prevailing climatic situation can be done by planting breeder seed crop during 1 week of November in Gwalior region of north central India.